The analysis of China cross-border e-commerce - Sa, Yayun (My University, 2019)
Bilgi ve iletişim teknolojisinin hızlı gelişimi, insan toplumunun yaşamında büyük değişiklikleryaptı ve ticari alanda yeni bir e-ticaret modelini teşvik etti. Bugünün hayatında, farklıülkelerden gelen ve farklı dilleri konuşan ve farklı kültürleri olan artan sayıda insanın,Alibaba.com, Aliexpress. com JD. com, Lightinthebox gibi Çin sınır ötesi e-ticaretplatformlarında mal satın alma veya satma olasılığı yüksektir. İnternet teknolojisininavantajlarına ve Çin yerel e-ticaret pazarının hızlı gelişmesine bağlı olarak, Çin sınır ötesi eticarethacmi % 30'un üzerinde bir büyüme oranı ile gelişmektedir. B2B, B2C, O2O ve C2Cpltformlar ile Çin sınır ötesi e-ticaret işlem hacmi 2018'de 9, 6 trilyon yuan olmuştur ve 2020'deÇin dış ticaretinin% 40'ını oluşturacak şekilde 12 trilyona ulaşması beklenmektedir. 2008küresel mali kriziyle aynı zamanda, geleneksel büyük sınır ötesi ticaretin bir kısmını küçük sınırötesi e-ticaret işlemlerine dönüştürüyor. Sınır ötesi e-ticaret, internet çağının yeni bir ekonomikbüyüme noktasıdır ve Çin'in dış ticareti için yeni fırsatlar ve zorluklar getirmiştir. Bu yüzden,Çin sınır ötesi e-ticaretinin analizi, küresel şirketler ve diğer ülkelerin Çin ile ticaret ilişkisigeliştirmeden önce durumlarını anlamalarına yardımcı olacaktır. Aynı zamanda diğer ülkelerinkendi sınır ötesi e-ticaretinin gelişmesine yönelik çalışmaları içinde yararlı olabilir. Bu tezinamacı, Çin sınır ötesi e-ticaretinin genel bir analizini vermektir. Bu amacıla ürün kategorileri,işletme modelleri ve platformları, ödeme sistemi, gümrükleme ve gibi pekçok konuincelenmiştir . Ayırca Çin sınır ötesi e- Genel bir SWOT analizi uygulayarak ticaret. Bu nedenle,bu çalışmanın sonuçları sınır ötesi e-ticaret çalışmalarına örnek oluşturacaktır.

Rapid development of information and communication technology has made great changes inthe life of human society and this has stimulated a new e-commerce model in the commercialfield. In today’s life, an increasing number of people coming from different countries andspeaking in different languages with different cultures are likely to purchase or sell goods onChinese cross-border e-commerce platforms like Alibaba.com, JD. com, Lightinthebox. com,DHgate. com. Combined with the advantage of the economics of scale in the internet world andthe good performance of China e-commerce market, China cross-border e-commer is growingwith over 30% growth rate. The transaction volume of China cross-border e-commerce was 9.6 trillion Chinese yuan in 2018 and is expected to reach to 12 trillion Chinese yuan in 2020which will account for 40% of China foreign trade. The speed rise of cross-border e-commerceis own to the rapid development of information network technology and global economicintegration, in coincidence with the 2008 global financial crisis making some of the traditionallarge cross-border trade into small online transactions. Cross-border e-commerce is a neweconomic growth point of the internet era and has brought new opportunities and challenges forChina's foreign trade. Therefore the analysis of China cross-border e-commerce will be helpfulfor global enterprises and other countries to understand the whole situation of China crossbordere-commerce before they want to establish trade relationship with China . Beside theanalysis of China cross-border e-commerce also can benefit the study of others countries’ owncross-border e-commerce’s development. The aim of this paper is to give a general analysis ofChina cross-border e-commerce by basing on reviewing the details related to it background,product categories, business models and platforms, payment system, custom clearance andtaxation reform and so on. This paper will also list the weakness, strengths, opportunities andthreats of the cross-border e-commerce in China and do a general SWOT analysis. Thereforethe results of this study will be recommendable for similar studies in cross-border e-commercestudy area.
Keywords: Cross-border E-commerce(CBEC); Finance; International trade; Maliye; Sınır ötesi E-Ticaretinin，SWOT Analizi， Uluslararası Ticaret International trade; SWOT analysis; Uluslararası ticaret